Modeling the rapid spread of avian influenza (H5N1) in India - Arni S.R. Srinivasa Rao (Mathematical Biosciences and Engineering)
Controlling the spread of avian bird flu has become a challengingtasks for Indian agriculture and health administrators. After the first evidenceand control of the virus in 2006, the virus attacked five states by January2008. Based on the evidence of rapid spread of the avian bird flu type H5N1among the Indian states of Maharashtra, Manipur, andWest Bengal, and in thepartially affected states of Gujarat and Madhya Pradesh, a model is developedto understand the spread of the virus among birds and the effect of controlmeasures on the dynamics of its spread. We predict that, in the absence ofcontrol measures, the total number of infected birds in West Bengal withinten and twenty days after initial discovery of infection were 780,000 and 2.1million, respectively. When interventions are introduced, these values wouldhave ranged from 65,000 to 225,000 after ten days and from 16,000 to 190,000after twenty days. We show that the farm and market birds constitute themajor proportion of total infected birds, followed by domestic birds and wildbirds in West Bengal, where a severe epidemic hit recently. Culling 600,000birds in ten days might have reduced the current epidemic before it spreadextensively. Further studies on appropriate transmission parameters, contactrates of birds, population sizes of poultry and farms are helpful for planning.